Foreword* - Larsen, Kim; Shimomura, Michitaka (Zootaxa, 2007)
Humanity has always been fascinated by organisms which survive in the most extreme and hostile environments and one such environment, is the hadal depths of the ocean trenches. Life can exist here in a food deprived habitat at enormous pressure and as far from the sun as possible, and yet it thrives. Which kinds of organisms can are found there and where did they come from? Is it a refuge for old phylogenetic lines elsewhere gone extinct or is it a habitat for highly specialized species? Considering that the trenches constitute only a minor part of the deep sea, the trenches have received the lion’s share of scientific attention. The first ‘Trench’ exploration consisted of depth soundings made during the Challenger expedition in 1872-1876, but biological deep sea sampling started in earnest with the Danish Galathea expedition II 1950-1952 which managed to make collections at the deepest parts of the trenches. Even today the trenches hold many mysteries although the focus has changed somewhat from biology to biochemistry, especially carbon sequestration (Shirayama 1997; Takeuchi et al. 1999; Nakamura & Inagaki 2005).